A method for measuring cholinesterase activity in human saliva and its application to farmers and consumers - Thiphom S. (2014)
In the present study, we aimed to find alternative biomarkers for organophosphorus and carbamate pesticide exposure. Saliva has been suggested as an ideal body fluid besides blood. The Ellman method was modified to make it suitable for detecting salivary cholinesterase (SChE). The activities of salivary acetylcholinesterase (SAChE) and salivary butyrylcholinesterase (SBChE) were measured indirectly by quantifying the concentration of 5-thio-2-nitrobenzoic acid ions formed in the reaction between the thiol reagent 5,5′-dithiobis-2-nitrobenzoic acid and thiocholine, a product of substrate hydrolysis by ChE. In the present study, a colorimetric method was modified to measure SChE activities using two different substrates, acetylthiocholine iodide for total SChE and a specific substrate, butyrylthiocholine iodide for SBChE in the same sample. The modified methods were applied to measure SAChE and SBChE activities and then compared with red blood cell AChE (RAChE) and plasma BChE (PBChE) activities in blood. One hundred farmers (50 females, 50 males) and 100 consumers (50 females, 50 males) were randomly recruited from the Fang district's agricultural area, Chiang Mai province. In consumers, the medians of the SAChE, SBChE, RAChE and PBChE levels were 4.03 mU mL-1, 4.17 mU mL-1, 4.18 U mL-1 and 4.28 U mL-1, respectively, while the medians in farmers were 3.94 mU mL-1, 4.25 mU mL-1, 3.95 U mL-1 and 4.16 U mL-1, respectively. Although SBChE levels are significantly lower (approximately 1000 times) than PBChE levels, SBChE was not influenced by any factors which cause variability in the activity of enzymes, i.e. hypertension, hyperlipidemia, diabetes and taking the contraceptive pill. Moreover, amongst consumers who were less exposed to pesticides, there was no variability in low level detection of SBChE because the present study found a correlation (r = 0.232, P = 0.020) between the activity of SBChE and PBChE only in consumers. Therefore, SBChE may be an alternative biomarker for pesticide exposure besides PBChE in consumers. The modified methods in the present study had sufficient sensitivity with a low limit of quantitation and high accuracy when applied to measure activities of SChE with low within-day coefficients of variation (%CV) by the intra-assay, and between-day %CV by the inter-assay for all enzymes. However, a more sensitive method should be developed in a further study to measure the relatively low activities of SAChE and SBChE among ChE inhibited farmers. © 2013 The Royal Society of Chemistry.